2020
DOI: 10.1002/14651858.cd010904.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline versus other intracranial pressure-lowering agents for people with acute traumatic brain injury

Abstract: Hypertonic saline versus other intracranial pressure-lowering agents for people with acute traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…The implications of this on final outcome of these patients remain unclear: although a (prolonged) raised ICP has been shown to be associated with a worse outcome, a proven survival benefit has never been established for hyperosmolar therapy in patients with TBI. [18][19][20] As we found that specificity of clinical signs for a raised ICP is high, overtreatment (with a resulting risk of development of acute heart failure, pulmonary oedema and the possibility of developing central pontine myelinosis) 21 is less of a concern when treatment guidelines are followed.…”
Section: Discussionmentioning
confidence: 77%
“…The implications of this on final outcome of these patients remain unclear: although a (prolonged) raised ICP has been shown to be associated with a worse outcome, a proven survival benefit has never been established for hyperosmolar therapy in patients with TBI. [18][19][20] As we found that specificity of clinical signs for a raised ICP is high, overtreatment (with a resulting risk of development of acute heart failure, pulmonary oedema and the possibility of developing central pontine myelinosis) 21 is less of a concern when treatment guidelines are followed.…”
Section: Discussionmentioning
confidence: 77%
“…Though mannitol has long-been the workhorse hyperosmolar therapy, a growing body of literature suggests that hypertonic saline is also effective in treating elevated intracranial pressure from a variety of causes (12). Although it has been suggested that hypertonic saline may be superior to mannitol in terms of rate, duration, effect size, and side effect profile, controversy remains (13)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reviews and meta-analyses evaluate HTS and mannitol against various agents in the human clinical literature (33,62,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). In summary, the studies are heterogenous in population, dose, concentration and rate of fluid administered, therapeutic targets, and outcomes of interest.…”
Section: Managing Elevated Icp With Osmotherapymentioning
confidence: 99%
“…A rebound phenomenon was defined in a Cochrane review by Chen (76) et al as 'intracranial pressure rising above its original level after hyperosmolar therapy.' However, the rebound phenomenon occurring in patients with TBI is only mentioned in passing in a single study included in the Cochrane review (76) and in the veterinary pilot study (71). Despite effective reduction of ICP, neither HTS nor mannitol has clinical evidence supporting improved survival or long-term neurologic outcome (33,75,81).…”
Section: Managing Elevated Icp With Osmotherapymentioning
confidence: 99%